School Shootings and Student Performance - Poutvaara, Panu
In this paper, we study how high school students reacted to the shocking news of a school shooting. The shooting coincided with national high-school matriculation exams. As there were exams both before and after the shooting, we can perform a difference-in-differences analysis to uncover how the school shooting affected the test scores compared to previous years. We find that the average score of young men declined due to the school shooting, whereas we do not observe a similar pattern for women.school shootings, school performance, shocking news, gender differences, treatment effect models